(untitled) (Journal of the College of Basic Education, 2023)
Contemporary studies are preoccupied with poetic rhythm, as it represents a vital aspect in the structurepoetic and in the depth of the significance, and these studies tried to reach the elements of the rhythmic structureAnd its components down to the poet’s poetic pauses and emotional tensions.A careful review of the many opinions that dealt with rhythm confirms the serious importanceFor rhythm in poetry, it constitutes an essential axis in the introductory poetry, as it is “the first condition for the emancipation ofThe artist and his deviance from the rules followed in the use of ordinary communication tools and his discovery of his toolsprivate” (1).We must indicate a number of these concepts in order to form an accurate picture of it.Rhythm is “an arrangement of the vocal characteristics or some of them in a specific pattern, so that they echo in the stylespeech over equal or responsive temporal distances... and from the sum of this frequency passed inRhythm form consists of one verse” (2), and this means that rhythm is the simplest form ofWeight in the sense that it adopts a precise arrangement of vocabulary words with similar sound characteristics orare arranged with each other at equal intervals of time. Others believe that the rhythm“It is represented by the taf’ila in the Arabian Sea. The movement of each taf’ila represents the unit of the house’s rhythm. As for the meter, it is(3) The tafa’ila is a rhythmic unit adopted by Al-Bahr.The verbs form equal units of time with motions and rests that form the core of time.Rhythm, and for others, rhythm represents an instinctive system based on feeling and emotion that leads to it.instinct, it is “a repetition and a harmonious alternation of syllables that the poet feels instinctively.”instinctively.” (4).poet in all parts of the literary work by dividing it into distinct units that are repeated over and over again.A monotonous arrangement that combines the art of poetry with its most important pillars, which is partial music and general music.